Vitamin A supplementation for the reduction of the risk of mother-to-child transmission of HIV. Issue 7 (July 2015) - McHenry, Megan S; Apondi, Edith; Vreeman, Rachel C
<x xml:space="preserve">Abstract</x> Although advances in HIV prevention and treatment suggest the possibility of creating an AIDS-free generation, many areas of the world still suffer from high rates of mother-to-child transmission (MTCT) of HIV. Interventions proven to significantly decrease rates of MTCT of HIV are often unavailable in resource-limited settings due to lack of reliable clean water, low numbers of hospital deliveries and inconsistent availability of antiretroviral medications. Vitamin A, with its multiple roles in epithelial, reproductive and immune function, has been evaluated as a possible intervention for preventing MTCT. Early observational studies suggested an association between vitamin A deficiency and increased rates of MTCT of HIV; however, the controlled studies that followed did not find a benefit for vitamin A in decreasing MTCT rates. Although vitamin A has some benefits for infants postpartum, it is not recommended for the reduction of the risk of MTCT of HIV.